Analisis Tantangan Moderasi Beragama di Era Digital melalui Perspektif Teori Filter Bubble dan Echo Chamber - Alfi Rohmatul H; Moh. Asaddin Nur (Jurnal Sosial Humaniora, 2024)
The digital era has revolutionized social interactions, including discussions onreligious issues, through digital platforms. However, platform algorithms oftenfoster filter bubbles and echo chambers, limiting access to diverse informationand intensifying social polarization. Filter bubbles expose users only to contentaligning with their views, while echo chambers amplify these views withoutengaging alternative perspectives. These dynamics pose challenges to interfaithdialogue and threaten religious moderation in Indonesia, a nation characterizedby its vast religious diversity. This article examines these challenges using theconcepts of filter bubbles and echo chambers as analytical lenses, focusing onhow algorithms exacerbate polarized religious understanding and hinderopenness to differing views. To address these issues, a comprehensive approachinvolving society, government, and digital platforms is essential. Enhancingdigital literacy within society can cultivate critical thinking and openness todiverse perspectives. The government must establish policies promotinginterfaith dialogue and curbing divisive content. Simultaneously, digitalplatforms should design algorithms that prioritize inclusivity, introduce variedperspectives, and foster harmonious interactions. Collaboration among thesestakeholders can create a digital environment that upholds religious moderation,supports unity in diversity, and mitigates the risks posed by algorithm-drivenpolarization.